Proximate Composition of Street Snacks Purchased from Selected Motor Parks in Lagos - Pikuda, O.O.; Ilelaboye, N.O.A. (Pakistan Journal of Nutrition, 2009)
In developing countries, street food including commercially produced snacks sold by street vendors are widely consumed by millions of people and they are sources of affordable nutrients to many sectors of the population. Snacks made by vendors on-site were purchased from five different motor parks along Agege motor road in Lagos and were analyzed for their proximate composition using standard analytical methods. The result indicated that fried yam had the highest moisture content 51.48-55.73 g/100 g while the fish roll had the lowest moisture content 11.49-555.73 g/100 g while the fish roll is the richest in protein 16.80 g/100 g.-18.83 g/100 g, with fried plantain having lowest protein content 3.49-3.84 g/100 g, the fat content of roasted yam 1.9-1.94d/100 g is the least and that of fish roll is the highest 15.24-16.49 g/100. Ojuelegba roasted yam has the highest fibre content 8.49 g/00 g and the lowest fibre content 0.14 g/100 g found in Mushin. Roasted plantain contain the highest carbohydrate (61.58 g/100 g Mushin), while the lowest found in Ojuelegba fish roll 28.87 g/100 g, fish roll purchased from Oshodi have the highest ash content 5.15 g/100 g, fish roll gave the highest energy value (403.60-415.19 Kcal). It was concluded that although the proximate composition of snacks purchased from the same location are significantly different, but the location of purchase has no significant effect on the proximate composition of individual snack.